Agreement on legal assistance: legal regulation of the “success fee” in the Republic of Kazakhstan - Zhamburbayeva, S. (Bulletin of the Karaganda University “Law Series”, 2023)
The article is devoted to the study of the current legal regulation of the contract for the provision of legal assistance in the Republic of Kazakhstan, namely, the prohibition of the legislator on contracts that make the amount of payment for legal assistance provided by advocates dependent on the outcome of the case or the success of advocacy, also referred to as “success fees”, or contracts under which the lawyer receives part of the awarded amount. The paper draws attention to the difference between the regulation of the procedure for concluding paid contracts by advocates / lawyers and legal consultants, despite the fact that these subjects are equally admitted by the legislator to representation in civil proceedings. The author conducted a study and analysis of the opinions of various authors in order to understand the possible reasons for such a categorical point of view of the legislator in relation to the “success fee”, a comparative analysis is carried out between the norms of the Anglo-Saxon and Romano-Germanic systems of law in relation to this type of payment for services and remuneration, and also assesses the risk of the principal's refusal to fulfill his duty to payment for services rendered by a representative after receiving the desired positive result. In order to improve the Law “On Advocacy and Legal Assistance”, the author summarizes the need to introduce appropriate positive changes.